PENYULUHAN PENDAFTARAN MEREK ONLINE DALAM USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI LINGKUNGAN KARANG TARUNA PADALARANG KABUPATEN BANDUNG BARAT - Wahyudi Wahyudi; Ananda Putri Nur Amalia (Jurnal Al Basirah, 2021)
This community service activity is organized by the Faculty of Law, Indonesian Computer University in collaboration with the Youth Organization Management, Padalarang District, West Bandung Regency. In the midst of the COVID-19 pandemic, the products of Micro, Small and Medium Enterprises (MSMEs) of the Padalarang District community continue to grow and become more diverse and almost every product has a brand, but the MSMEs brand owned has not been registered with the Directorate General of Intellectual Property. The method used is to conduct legal counseling through the media zoom meeting. The use of brands on MSMEs products can add higher selling value compared to unbranded products, MSMEs actors can be harmed if their products are used and even imitated in whole or in part by others because they sell well in the market. However, MSMEs actors cannot prevent and even sue because the mark has not been registered. Trademark registration is a must for MSME actors if they want to protect their rights to the mark. Trademarks to be registered are quite easy to use by utilizing online trademark registration, specifically for the registration of trademarks for MSMEs actors, the fees charged are lower than those of industrial marks. The legal protection of registered trademark rights is for 10 years and can be extended for the same time.